Draft 11th Five Year Plan (2007-12) and Draft Annual Plan (2007-2008) Part-III Government of Tripura - Planning Commission (Planning Commission, 2007)
Draft 11th Five Year Plan (2007-12) & Annual Plan-2007-08- Proposed outlays Major/Minor Head & scheme-wise Draft 11th FY Plan (2007-012) & Annual Plan 2007-08-proposed outlays Physical Targets and Achievements Statement Regarding Externally Aided Projects Baharat Nirman Programmes Centrally Sponsored Schemes Draft 11th FY Flan (2007-12) &Annual Plan 2007-08 : Financial outlay : proposal for TSP Draft 11th FY Plan (2007-12) &Annual Plan 2007-08- physical target and Achievement: proposal for TSP Draft 11th FY Plan (2007-12) &Annual Plan 2007-08-Financial outlay proposal for SCSP Draft 11th FY Plan (2007-12) &Annual Plan 2007-08-Physical Target & achievement : proposal for SCSP Draft 11th FY Plan (2007-12) &Annual Plan 2007-08-Financialoutlay : proposal for WC.
Planning (P&C) Department